Usaha Budidaya Rumput Odot (Pennisetum Purpureum CV. Mott) - Siti Rochaeni; Lilis Putri Nuraeni; Rizki Adi Puspita Sari (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Green fodder is the main food source needed for ruminants. One type of fodder that can be selected as an alternative is dwarf elephant grass (Pennisetum purpureum cv. Mott). The need for dwarf elephant grass is a business opportunity in utilizing existing land to run the dwarf elephant grass cultivation business because grass feed is always needed fresh and in large quantities. The aims of this study were (1) to analyze the structure of the costs incurred in the dwarf elephant grass cultivation business, (2) to analyze the income of the dwarf elephant grass cultivation business, and (3) to analyze the financial from the dwarf elephant grass cultivation business. The data source uses primary data obtained by direct observation and interviews with company owners and managers. Secondary data obtained from the company's financial data and other data derived from the literature. The results of the study show that (1) the largest variable expenditure component in running an dwarf elephant grass cultivation business is labor costs and the smallest cost component is land and building tax (PBB). (2) the business income of dwarf elephant grass cultivation for a year is profitable. (3) The financial analysis indicates that the business will experience a return on capital for 6 months.